2016
DOI: 10.1111/cch.12323
|View full text |Cite
|
Sign up to set email alerts
|

Choosing foods for infants: a qualitative study of the factors that influence mothers

Abstract: Choosing foods for infants is a complex social practice. An ecological framework depicting the multiple influences on what people eat and sociological theory on food choice regarding the role of 'social structure' and 'human agency' are both applicable to the process of choosing foods for infants. Equity issues may be key regarding the degree to which mothers can choose particular foods for infants (e.g. choosing foods which promote health).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 38 publications
3
72
0
Order By: Relevance
“…Likewise, Walsh et al () described that mothers experience challenges in food choice when extended family members, with different views on giving snacks, are present. Similarly, Boak et al () concluded that the presence of others, like grandparents, extended family, or friends, could have an influence on foods mothers choose for their infants. Pettigrew and Roberts () reported that mothers feel undermined by their spouse or other direct family in their ability to control the quality of their child's diets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Walsh et al () described that mothers experience challenges in food choice when extended family members, with different views on giving snacks, are present. Similarly, Boak et al () concluded that the presence of others, like grandparents, extended family, or friends, could have an influence on foods mothers choose for their infants. Pettigrew and Roberts () reported that mothers feel undermined by their spouse or other direct family in their ability to control the quality of their child's diets.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, mothers would like to make the best choices for their child, and therefore, they could experience difficulties and feelings of doubt (Fielding‐Singh, ; Gram, Hohnen, & Pedersen, ; Johnson, Sharkey, Dean, Alex McIntosh, & Kubena, ; Machín, Giménez, Curutchet, Martínez, & Ares, ). In fact, mothers wish to combine healthy food choices, with their child's taste preferences (Boak et al, ; Carnell, Cooke, Cheng, Robbins, & Wardle, ; Damen, Luning, Fogliano, & Steenbekkers, ; Walsh et al, ; Wijtzes et al, ), two values that often conflict (Luomala et al, ). To which extent value conflicts occur in snack choice has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Mothers (and other caregivers) therefore play a vital role in determining children’s early experiences with food and eating. However, evidence also suggests that the mother’s food choice for her infant is dependent both on cultural and familial beliefs and attitudes and also on the affordability of foods [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the ADG and IFG offer nutritional evidence to inform and support healthy lifestyles, it appears that other approaches may also be required including clear, distinct and unique behaviour change models for individuals and populations (Boak et al, 2016; Hoare et al, 2014).…”
Section: Discussionmentioning
confidence: 99%